BUDI DAYA SAYURAN DENGAN HIDROPONIK SEBAGAI SOLUSI DALAM MEWUJUDKAN EFEKTIVITAS DAN EFISIENSI SERTA KEBERLANJUTAN PERTANIAN - Lalu Takdir Jumaidi; Sidiaji, Habib; Agustina, Syarifa; Aziza, Nida Maulana; Roshada, Amrina; Haerunnisa, Haerunnisa; Patmawati, Patmawati; Zulmawati, Baiq Risa; Lage, Tabah Surying; Burdawani, Amirul Mujaddid; Mausulin, Silman (Jurnal Wicara, 2025)
Socialization activities regarding organic farming with a hydroponic system to encourage the community to develop the potential for advanced and sustainable agricultural systems in Sakra Timur village. The purpose of this activity is to provide understanding and training to the community with practical skills that can be applied in everyday life with the hydroponic system method. The methods used include lectures, discussions, questions and answers, and demonstrations. The results of the activity showed that the number of participants was in accordance with the expectations of the Pengabdi team, which was 30 people. The results of this activity ran successfully and smoothly, reflected in the enthusiasm of the participants throughout the event. The enthusiasm of the participants can be seen from the seriousness of the community in listening to the material and active involvement in the question and answer session.